Topological modification of the electronic structure by Bi-bilayers lying deep inside bulk Bi2Se3. (8th February 2016) - Lee, Paengro; Kim, Jinwoong; Kim, Jin Gul; Ryu, Min-tae; Park, Hee-min; Kim, Namdong; Kim, Yongsam; Lee, Nam-Suk; Kioussis, Nicholas; Jhi, Seung-Hoon; Chung, Jinwook
Abstract: We observe the modified surface states of an epitaxial thin film of a homologous series of (Bi2 )m (Bi2 Se3 )n, as a topological insulator (TI), by angle-resolved photoemission spectroscopy measurements. A thin film with m : n = 1 : 3 (Bi8 Se9 ) has been grown with Bi2 bilayers embedded every other three quintuple layers (QLs) of Bi2 Se3 . Despite the reduced dimension of continuous QLs due to the Bi2 heterolayers, we find that the topological surface states stem from the inverted Bi and Se states and the topologically nontrivial structures are mainly based on the prototype of 3D TI Bi2 Se3 without affecting the overall topological order.